Inter-rater and intra-rater reliability of head-mount laser device on assessing cervical spine proprioception in patients with cervicogenic headache - Prakash, Jayabalan; Nagarani, R.; Bhojan, Kannabiran; Shalini, Catherine R.; Reddy, Ravindra C.; Chittybabu, Dharshini; James, Tittu Thomas (International Journal of Research in Medical Sciences, 2024)
Background: Relationship exist between the occurrence of cervicogenic headache (CGH) and head posture, due to a reduction in proprioception from the cervical spine. Active joint position sense of the cervical spine can be assessed using head-mount LASER device. This study evaluated the reliability of the head-mount LASER device in assessing cervical proprioception in adults with CGH. Methods: A total of 50 adults of both genders with a clinical diagnosis of CGH were recruited for the study. The assessment for cervical proprioception was done using the device using a pre-determined test protocol, by two different therapists. The tests were repeated on the next day as well. The accuracy of relocation of the LASER pointer from the pre-determined target spot were evaluated in centimeters, during both flexion and extension. Results: The study found good inter-rater reliability for flexion (ICC=0.888; 95% CI: 0.743 to 0.945) and extension (ICC=0.873; 95% CI: 0.754 to 0.931), and good to excellent intra-rater reliability for the device (ICC for flexion and extension being 0.952 and 0.951, respectively). Conclusions: This study concluded that head-mount LASER device can be used as a clinical tool in assessing cervical proprioception, and demonstrated good inter-rater and intra-rater reliability when used on patients with cervicogenic headache.